CHARACTERISTIC OF (AgI)0.44 (LiI)0.22 (AgPO3)0.34 IONIC CONDUCTOR PREPARED BY MELT QUENCHING METHOD - Makhsun Makhsun; T. Sakuma; E. Kartini (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2014)
CHARACTERISTIC OF (AgI)0.44 (LiI)0.22 (AgPO3)0.34 IONIC CONDUCTOR PREPARED BY MELT QUENCHING METHOD. Characterization of (AgI)0.44 (LiI)0.22 (AgPO3)0.34 ionic conductor prepared by melt quenching method have been carried out by using X-RayDiffractometer (XRD), Differential Scanning Calorimeter (DSC) and Inductance (L) Capacitance (C) Resistance (R) meter. X-ray diffraction pattern shows that the compound has a mixture of amorphous and small amount of crystalline formwith several Bragg peaks correspond toAgI. The DSC thermograph shows that an endothermic peak at temperature 420 K matches with the phase transition ofAgI which reinforces that a number ofAgI are not dissolved in the material of (AgI)0.44 (LiI)0.22 (AgPO3)0.34 . The obtained dc ionic conductivity is around 10-2 S/cmat ambient temperature. The activation energy has two values, 0.20 eV below 380 K and 0.15 eV above 380 K.